Rural roads and urban agglomeration economies: benefits for town and country? - Bell, Clive (Working paper, 2018)
Do urban agglomeration economies enhance the social profitability of rural roads? When all goods are traded at parametric world prices, lower transport costs benefit villagers. Urban activities and welfare are unaffected if labour is immobile, but their levels fall when rural workers move freely to take up urban jobs while remaining members of their extended families. In a closed, two-good economy with mobile labour, the effects of agglomeration economies depend on the substitutability of rural and urban goods. With a Cobb-Douglas rural technology, aggregate benefits are substantially greater in the presence of empirically plausible elasticities of agglomeration economies when preferences are Cobb-Douglas and urban households' tastes for urban goods are somewhat stronger than those of rural households. When the goods are rather poor substitutes, these enhancing effects are quite small. In an open economy with a single nontradeable whose production is relatively labour-intensive, improved rural roads will likely induce a fall in urban welfare in the presence of agglomeration economies, even with Cobb-Douglas preferences and immobile labour.